ملامح تأثير الإسلام على تفسير العبادات اليهودية في العصر الوسيط - حسين, عبد الستار عدنان (lark, 2019)
abstractThe translations of the Bible (the Bible and the Bible) have historically been turning points within the cultures that it produced - with its linguistic structures of the Greek Septuagint, the Aramaic Targum, the Syriac alphabet, the Latin dialect, etc. The Christian and Jewish communities that benefited from these great works Incorporate the verses of their sacred religious writings into their scientific, ritual, and even general discourse. In other words, written translations constituted the self-identity of Jews and Christians, and allowed them to express the sacred in innovative ways. For many, the goal was not to translate the word text into a word, but rather to translate the text from within the semantic environment and the literal contexts of the target language. This reality is especially true of the Hebrew interpretation of the Hebrew Bible at the turn of the twentieth century. This illuminating research, by adopting the comparative historical approach, will shed light on some of the semantic and lexicological elements in Moses' five books, which the modern scholars did not try to translate and analyze in depth in this sacred text .